Penerjemahan Teks Astronomi: Strategi dan Variasi Penerjemahannya - Retno Hendrastuti (Kelasa, 2018)
There are problems in translating  the astronomy text from English to Indonesian. The astronomy text has special term that common people do not understand. This paper tries to explore the strategies and translation variation of astronomy text translation. The data are taken from quesionaire about problems, strategies, and translation results from three translator respondants. The study results showed that there were three main problems in astronomy text translation, those were translating special terms, the name of certain institution and stuffs, and long phrases and sentences. To translate special terms they were using dictionary (general and special), using parallel texts, borrowing and description technique. To translate the name of certain institution and stuff they were using borrowing and description technique. Then, for long phrases and sentences they were identifying the type and function of each component and breaking it down into two clouses or more, before translating it using literal and other techniques. Then, there were two translation variations, those were translation for certain people (academic and proffesional) and translation for common people.  AbstrakAda beberapa kendala dalam menerjemahkan teks astronomi dari bahasa Inggris (BSu) ke bahasa Indonesia (BSa). Ini karena teks astronomi mempunyai istilah khusus yang jarang diketahui kalangan awam. Tulisan ini menggali strategi dan variasi penerjemahan teks astronomi. Data bersumber hasil isian kuesioner mengenai kendala, strategi, dan hasil penerjemahan dari tiga responden penerjemah. Hasil kajian menunjukkan beberapa strategi untuk tiga permasalahn utama dalam penerjemahan teks astronomi. Pertama, menggunakan kamus (umum dan khusus), teks paralel, teknik peminjaman, dan teknik deskripsi untuk menerjemahkan istilah khusus. Kedua, menggunakan teknik peminjaman dan teknik deskripsi untuk menerjemahkan nama lembaga serta alat khusus. Terakhir, mengidentifikasi jenis dan fungsi masing-masing komponen serta memecah klausa menjadi dua klausa atau lebih sebelum menerjemahkan secara harfiah dan teknik penerjemahan yang lain untuk menerjemahkan frasa atau klausa yang panjang. Kemudian, ada dua variasi hasil penerjemahan, yaitu terjemahan untuk kalangan khusus (akademik dan profesional) dan terjemahan untuk kalangan awam.